A causal model of green supply chain management for manufacturing industry - Mohamed, Norhafiza (2023)
Requirements and needs from stakeholders, government, non-government agencies and competitive market environment have urged manufacturing industries to implement the Green Supply Chain Management (GSCM) initiatives, such as increase the used environmentally friendly material, optimizing the process as well as awareness related to environmental issues and etc. in their operation. The successful implementation of GSCM is important, mainly to increase the economic performance and sustainable of business. There are various factors, external and internal, that are associated with Supply Chain Management (SCM) in planning and executing the concept of GSCM. Therefore, the awareness on its long-term effect of implementation in terms of practices, strategies and benefits can be obtain should be always prioritised. The roles of each factor and the relationship among factors is important in implementing GSCM. Lack of focus to understand these factors is perceived to increase the difficulties in implementing a better GSCM practices. Using Multicriteria Decision-Making (MCDM) method, each factor that contributes to managing GSCM practices has been studied. The results then used to evaluate the important factors in GSCM practices, mainly to give a better understanding based on causal relationship amongst the identified factors. In this research, main data were gathered from survey involving 241 manufacturing companies in Malaysia. From the survey, sixty-one (26.14%) questionnaires were returned and used for further analysis using the IBM SPSS software version 16. From factor analysis, one factor has been identified representing Work System Performance (WSP). The Work Responsive Practices (WRP) consists of three main factors, namely Quality Control (QC), Process Management (PM) and Evaluation Management (EM). While, for Strategic Environmental Practices (SEP), three factors has been identified, namely Recycling Commitment (RC), Natural Usage (NU) and Optimisation of Usage (OU). The Profits (PR) and Reputation (RP) were the two factors representing Manufacturing System Achievement (MSA). As for Green Supplier Strategy (GSS), there were two factors identified, which were Guiding Supplier (GS) and Awareness (AW). Based on all these factors, a research model was developed using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach. Through DEMATEL all these factors then used in further analysis using ten pairwise questionnaires. The interrelationship among factors has been reviewed and validated by seven experts from manufacturing firms. This research model is significant as a references in providing the specific view to understand and considering the main factors in implementing the GSCM in the most effective way. This subsequently will assist industrial player as a guidance in determining the initiatives in implementation of an efficient GSCM in their manufacturing organisation.